Iron concentration of potato and sweetpotato clones as affected by location - Burgos, G.; Sosa, P.; Chacaltana, C.; Munoa, L.P.; Scurrah, M.; Salas, E.; Ccanto, Raul I.; Díaz, F.; Felde, T. zum (Elsevier, 2021)
The effect of growing location on the iron concentration of potato and sweetpotato as determined by ICP-MS was evaluated using freeze dried and milled samples from peeled raw potato tubers and sweetpotato roots. Significant variation of the iron concentrations due to genotype (clone or variety), location and genotype × location interaction was found for potato and sweetpotato. However, for potato, the iron concentration levels were mostly attributed to genotype which account for 62.89% of the total variance whereas for sweetpotato the iron concentration levels were mostly attributed to location which account for 76.16% of the total variance.